Upaya Meningkatkan Disiplin Guru dalam Kehadiran Mengajar di Kelas Melalui Penerapan Reward and Punishment di SMAN I ANAM RUTENG KABUPATEN MANGGARAI - Emanuel Adrianus Wagu (linguistic, literature, and teaching, 2023)
ABSTRAC The problems discussed in the research on Efforts to Improve Teacher Discipline in Teaching Attendance in Class through the Implementation of Rewards and Punishment at SMAN I Anam Ruteng Manggari Elementary School show that teachers' understanding in Efforts to Improve Teacher Discipline in Teaching Attendance in Class through the Implementation of Rewards and Punishment at SMAN I Anam Ruteng, Manggarai Regency, is still low. This study aims to describe the teacher's discipline in teaching attendance in class through the application of reward and punishment at SMAN I Anam Ruteng, Manggari district. The subjects of this study were teachers at SMAN I Anam Ruteng, Manggarai Regency. In this study the data collection technique used a test instrument. This test was used to determine the teacher's ability. The type of research used is descriptive qualitative research, the researcher collects data related to Teacher Discipline in Teaching Attendance in Class through the Implementation of Rewards and Punishment, then the data will be analyzed using the steps proposed by Miles and Hubermen namely, data reduction, data presentation, as well as drawing conclusions. The results of this study indicate that the application of Reward and Punishment is effective in increasing the discipline of teacher presence in class in teaching and learning activities. The data obtained shows that after implementing the action in the form of Reward and Punishment, there were 5 teachers who were late for more than 15 minutes, and teachers who were late for less than 10 minutes as many as 18 teachers. The application of Reward and Punishment can increase teacher discipline in attending class during teaching and learning activities at SMAN I Anam Ruteng, Manggarai Regency. Keywords: Ability, Teacher Discipline, Reward And Punishment